White superiority in Flannery O’connor’s The Barber and The Artificial Nigger - Aziz, Muhammad Fawzi Abdullah; Cahyawati, Erna; Sampurna, Hadi (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This research analyzes two short stories created by Flannery O’Connor entitled “The Barber” and “The Artificial Nigger” which depict the ideology of white superiority by scrutinizing the context of the stories and discussing the homology between the texts and the contexts. Data were analyzed using qualitative methods, and the theory used was genetic structuralism by Lucien Goldmann. Primary data concerning white superiority were taken from both short stories. Secondary data about socio-cultural and historical facts of white superiority in America in the 1940s -1950s were taken from journal articles and books. The research results show similarities between literary works and socio-historical conditions in the year when the literary works were written. The author’s worldview shows that she wants to represent the ideology of white superiority that has oppressed the black race. Through these short stories, the author wants to illustrate how cruel and difficult it is to fight the ideology of white superiority.